Ceramics of Ta-doping stabilized orthorhombic ZrO2 densified by spark plasma sintering and the effect of post-annealing in air. (15th March 2017) - Sponchia, Gabriele; Moshtaghioun, Bibi Malmal; Benedetti, Alvise; Riello, Pietro; Gómez-García, Diego; Domínguez-Rodríguez, Arturo; Ortiz, Angel L.
Abstract: 16 mol% Ta-doped ZrO2 powders were synthesized and densified by spark-plasma sintering (SPS) in vacuum, followed by post-SPS annealing in air, thus obtaining two ultrafine-grained ceramics consisting of Ta-doping stabilized orthorhombic ZrO2 . The as-SPSed ceramic is black because it is actually a suboxide essentially with reduced cations and abundant oxygen vacancies, whereas the post-annealed ceramic is white because it is an oxide without vacancies and with only partially reduced cations. Both ceramics are relatively hard and brittle, but the as-SPSed ceramic was slightly more so, attributable to crystallographic and microstructural differences. Implications of interest for the ceramics community are discussed. Graphical abstract: